IL‐7 germline variant: setting the stage for immune‐related adverse events. Issue 3 (24th February 2023) - Issaoui, Hussein; Ricci, Jean‐Ehrland
Abstract : Treatment with immune checkpoint inhibitors (ICIs) is frequently associated with immune‐related adverse events (irAEs). A new study identified an interleukin 7 (IL‐7) allelic variant—rs16906115—as a major risk factor for the development of ICI‐associated irAEs. This association is of great significance as it indicates that germline genetic variants influence the occurrence of irAEs, thus opening a new avenue for identifying high‐risk patients to enable better management of ICI therapy and associated irAEs. Abstract : During immune checkpoint inhibitor (ICI) therapies, some patients experience inflammatory side effects called immune‐related adverse events (irAEs). The authors of the new research discovered an IL‐7 allelic variant, whose presence in these patients' lymphocytes increases lymphocyte stability and leads to an active host immunity, as a major risk factor of developing ICI‐associated irAEs.